2008
DOI: 10.1504/jdr.2008.026987
|View full text |Cite
|
Sign up to set email alerts
|

Inspiration, images and design: an investigation of designers' information gathering strategies

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible.This is an author-deposited version published in: http://sam.ensam.eu Handle ID: .http://hdl.handle.net/10985/7602 To cite this version :Céline MOUGENOT, Carole BOUCHARD, Améziane AOUSSAT, Steve WESTERMANInspiration, images and design : an investigation of designers' information gathering strategiesJournal of Design Research -Vol. 7, n°4, p.331-351 -2008 Any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 11 publications
(14 reference statements)
2
62
0
2
Order By: Relevance
“…Many authors have found that companies struggle to achieve this integration (Bakshi and Fiksel, 2003;Dangelico and Pujari, 2010;Johansson, 2006;Le Pochat et al, 2007;Luttropp and Lagerstedt, 2006). In particular, companies find it difficult to integrate environmental considerations into the early stages of the NPD process because their existing NPD process is less formal in these early stages (Mougenot et al, 2008). This leads to the problem that management processes may only begin to encourage consideration of environmental factors later in the NPD process, by which point the opportunity to radically innovate is already passed (Tyl, 2011).…”
Section: Managementmentioning
confidence: 99%
“…Many authors have found that companies struggle to achieve this integration (Bakshi and Fiksel, 2003;Dangelico and Pujari, 2010;Johansson, 2006;Le Pochat et al, 2007;Luttropp and Lagerstedt, 2006). In particular, companies find it difficult to integrate environmental considerations into the early stages of the NPD process because their existing NPD process is less formal in these early stages (Mougenot et al, 2008). This leads to the problem that management processes may only begin to encourage consideration of environmental factors later in the NPD process, by which point the opportunity to radically innovate is already passed (Tyl, 2011).…”
Section: Managementmentioning
confidence: 99%
“…As we could observe in previous investigations [12], designers use external stimuli not only for analogical reasoning but also for emotional elicitation (Fig. 3).…”
Section: Emotional Elicitation By External Stimulimentioning
confidence: 74%
“…To support this common practice among designers, design-dedicated softwares or interfaces have been developed to retrieve images, such as ProductWorld [14], CRAI Interface [7], Cabinet [8], TRENDS [12]...…”
Section: Visual Stimuli In the Design Processmentioning
confidence: 99%
“…Due to limitations of space, we have not outlined all of the functionalities in complete detail, but an evaluation of the utility of the functionalities and the descriptions can be found in the paper of Bouchard et al(2008). Specifically, Mougenot et al (2008) and Bonnardel and Zenasni (2010) have conducted several empirical experimentations to explore the impact of the TRENDS system in terms of a creativity support tool. The work of Bonnardel and Zenasni (2010) showed that inspirational images provided by the TRENDS system allowed experience designers to produce creative ideas under the influence of their evocation of new concepts.…”
Section: Figure 12 Evolution Of Conception and Evaluation Processmentioning
confidence: 99%